Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.jpclett.1c02368
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Condensation in Molecular-Scale van der Waals Stacks

Abstract: Recent experiments have realized the Bose–Einstein condensation of excitons, known as exciton condensation, in extended systems such as bilayer graphene and van der Waals heterostructures. Here we computationally demonstrate the beginnings of exciton condensation in multilayer, molecular-scale van der Waals stacks composed of benzene subunits. The populations of excitons, which are computed from the largest eigenvalue of the particle-hole reduced density matrix (RDM) through advanced variational RDM calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…(See the Appendix for more details on how the signature of exciton condensation, λ G was computed.) This computational signature has been utilized to study exciton condensation is possible in quantum and molecular systems [29,[38][39][40]64]. One model known to achieve a large λ G value and hence exhibit exciton condensate character in the limit of a large correlation is the Lipkin quasispin model [15][16][17][18][19][20][21].…”
Section: B Exciton Condensationmentioning
confidence: 99%
“…(See the Appendix for more details on how the signature of exciton condensation, λ G was computed.) This computational signature has been utilized to study exciton condensation is possible in quantum and molecular systems [29,[38][39][40]64]. One model known to achieve a large λ G value and hence exhibit exciton condensate character in the limit of a large correlation is the Lipkin quasispin model [15][16][17][18][19][20][21].…”
Section: B Exciton Condensationmentioning
confidence: 99%
“…More recently, the author [10] showed that the complete N -representability conditions are derivable from convex combinations of higher-particle, constraint matrices. In the past decade approximate conditions have been employed in variational calculations of the 2-RDM to solve significant problems such as the elucidation of the electronic properties of a glassy, highly conductive amorphous polymer [38] and the revelation of exciton condensation in molecular analogs of double-layer graphene [39][40][41][42] (refer to Refs. [43][44][45][46][47][48] for their use in one-particle RDM functional theories).…”
Section: Introductionmentioning
confidence: 99%
“…Exciton condensation-a Bose-Einstein condensation of particle-hole pairs into a single quantum statehas generated considerable experimental and theoretical interest [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] due to the resultant superfluidity [20][21][22][23] of the constituent excitons (particle-hole pairs) allowing for the dissipationless transport of energy 24,25 , which presents the possibility for uniquely energy efficient materials. Further, the greater binding energy and lesser mass of excitonic quasiparticles relative to particle-particle Cooper pairs indicates that exciton condensation should occur at higher temperatures 26 relative to the temperatures at which traditional superconductivity-i.e., the condensation of particle-particle pairs into a single quantum state [27][28][29][30] -occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, van der Waal heterostructures 4,33,39,43 as well as graphene bilayers 17,31,44 demonstrate promise in the search for higher-temperature exciton condensate phases, with the tuneability of electronic states afforded by twisting graphene layers relative to each other being particularly of interest in recent literature 35,41 . a) Electronic mail: damazz@uchicago.edu Small, molecularly-scaled systems have also been revealed to support exciton condensation via theoretical explorations utilizing a signature of such condensation found in the modified particle-hole reduced density matrix (RDM) [8][9][10][11] . These molecular systems are able to be treated using theoretical approaches at lower computational costs and can be used as an analog for similar larger-scaled systems; moreover, molecular-scaled exciton condensation in and of itself may have potential applications in the design of more energy-efficient molecular-structures and devices.…”
Section: Introductionmentioning
confidence: 99%